Validation of Oil Trajectory and Fate Modeling of the Deepwater Horizon Oil Spill - Deborah P. French-McCay (Frontiers in Marine Science, 2021)
Trajectory and fate modeling of the oil released during the Deepwater Horizon blowout was performed for April to September of 2010 using a variety of input data sets, including combinations of seven hydrodynamic and four wind models, to determine the inputs leading to the best agreement with observations and to evaluate their reliability for quantifying exposure of marine resources to floating and subsurface oil. Remote sensing (satellite imagery) data were used to estimate the amount and distribution of floating oil over time for comparison with the model’s predictions. The model-predicted locations and amounts of shoreline oiling were compared to documentation of stranded oil by shoreline assessment teams. Surface floating oil trajectory and distribution was largely wind driven. However, trajectories varied with the hydrodynamic model used as input, and was closest to observations when using specific implementations of the HYbrid Coordinate Ocean Model modeled currents that accounted for both offshore and nearshore currents. Shoreline oiling distributions reflected the paths of the surface oil trajectories and were more accurate when westward flows near the Mississippi Delta were simulated. The modeled movements and amounts of oil floating over time were in good agreement with estimates from interpretation of remote sensing data, indicating initial oil droplet distributions and oil transport and fate processes produced oil distribution results reliable for evaluating environmental exposures in the water column and from floating oil at water surface. The model-estimated daily average water surface area affected by floating oil >1.0 g/m2 was 6,720 km2, within the range of uncertainty for the 11,200 km2 estimate based on remote sensing. Modeled shoreline oiling extended over 2,600 km from the Apalachicola Bay area of Florida to Terrebonne Bay area of Louisiana, comparing well to the estimated 2,100 km oiled based on incomplete shoreline surveys.